(untitled) (Journal of history, 2019)
The historical memory of the Great Patriotic War for over 75 years is still an important event in the historical memory of nations. The experience of the participation of men and women in the war, the experience of overcoming the difficulties of the military everyday life, accumulated by the generation of that time, seems relevant not only from research positions, but also from practical positions. It can serve as an example of overcoming the harsh trials of war, both by men and women. The memory of the past war is still one of the factors of the patriotic education of young people on the heroic examples of older generations, including such legendary personalities as Khiuaz Dospanova. The gender approach in historical research allows us to include in the research field a large number of new topics that have not attracted the attention of historians for a long time, which makes history richer and more diverse, allows it to include all groups of the population, makes history truly universal and popular. This article attempts to uncover the elders of the war with the participation of women in the wake of Hiuaz Dospanova’s memories.